2007
DOI: 10.4049/jimmunol.179.9.5886
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of IL-21 in B Cell Activation, Expansion, and Plasma Cell Generation during CD4+ T Cell-B Cell Collaboration

Abstract: During T cell-B cell collaboration, plasma cell (PC) differentiation and Ig production are known to require T cell-derived soluble factors. However, the exact nature of the cytokines produced by activated T cells that costimulate PC differentiation is not clear. Previously, we reported that costimulation of purified human B cells with IL-21 and anti-CD40 resulted in efficient PC differentiation. In this study, we addressed whether de novo production of IL-21 was involved in direct T cell-induced B cell activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
261
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(281 citation statements)
references
References 55 publications
(52 reference statements)
16
261
3
1
Order By: Relevance
“…1). As shown in this and other studies, CD40L costimulation with IL-21 induces robust plasmablast differentiation from both naive and memory B cells (19,27,114). Stimulation of naive B cells with BAFF or anti-IgM alone or each in the presence of IL-2 and IL-21, however, does not induce significant proliferation or differentiation.…”
Section: Discussionsupporting
confidence: 76%
“…1). As shown in this and other studies, CD40L costimulation with IL-21 induces robust plasmablast differentiation from both naive and memory B cells (19,27,114). Stimulation of naive B cells with BAFF or anti-IgM alone or each in the presence of IL-2 and IL-21, however, does not induce significant proliferation or differentiation.…”
Section: Discussionsupporting
confidence: 76%
“…BCR stimulation with Ag is not the only stimulation required for plasma cell differentiation. Stimulation with cytokines, such as IL-2, IL-4, IL-10, and IL-21, and contact-dependent engagement of CD40 on B cells by CD40L (CD154), expressed by activated CD4 + T cells, are required for plasma differentiation (22)(23)(24)(25)(26). Costimulation with these cytokines and T cells might prolong and enhance ERK1/2 phosphorylation and PAX5 phosphorylation and enable enough BLIMP1 expression to initiate plasma cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have documented that IL-21 stimulates B cell differentiation and IgG production, and a recent study demonstrated that IL-21 is required in B cell activation expansion and plasma cell generation during CD4 ϩ T cell-B cell interaction (15)(16)(17). Although, IL-21 has been shown to be a growth and survival factor in MM several years ago, no subsequent study has been devoted to the biological significance of the IL-21/IL-21R system in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IL-21 induces the differentiation of B cells into plasma cells through up-regulation of BLIMP1 (15). Moreover, a recent study demonstrated the requirement of IL-21 in B cell activation expansion and plasma cell differentiation induced by direct interaction of B cells with activated T cells (16). The role of IL-21 in regulating Ig production is supported by knockout mouse models.…”
Section: Ultiple Myeloma (Mm) 2 Is a Fatal Neoplasia Character-mentioning
confidence: 97%